Improving Behavioral Outcomes in Extension Using the Tools of Community-Based Social Marketing (CBSM) - Paul Monaghan; Martha Monroe (EDIS)
There is increasing evidence that, with the right approach, people can be encouraged to change. From recycling, composting, and picking up pet waste to saving water, the public is adopting new behaviors and giving up old ones. The tools to do this can be found in Community Based Social Marketing (CBSM). This 6-page fact sheet was written by Paul Monaghan and Martha Monroe, and published by the UF Department of Agricultural Education and Communication, September 2013. http://edis.ifas.ufl.edu/wc149